2021
DOI: 10.1371/journal.pone.0247833
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure to the urology surgeon during retrograde intrarenal surgery

Abstract: Retrograde intrarenal surgery is a common procedure that carries a risk of radiation exposure for urologists. This study aimed to measure the amount of radiation that urologists are exposed to during surgery, and to estimate how many procedures can be safely performed by one urologist per year. Variables that affect radiation exposure were also identified. Radiation exposure doses were measured for the eye, neck, chest, arms, and hands of a urologist who performed 226 retrograde intrarenal surgeries. To determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, few studies involve urologists during RIRS. A study by Park 8 demonstrated that a surgeon can perform up to 517 RIRS with appropriate radiation protection; however, this amount drops by 85% without shielding. Predictors for increased radiation exposure have been examined for percutaneous nephrolithotomy (PCNL), which suggests risk factors being an increased stone burden, staghorn calculi and longer procedural time 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, few studies involve urologists during RIRS. A study by Park 8 demonstrated that a surgeon can perform up to 517 RIRS with appropriate radiation protection; however, this amount drops by 85% without shielding. Predictors for increased radiation exposure have been examined for percutaneous nephrolithotomy (PCNL), which suggests risk factors being an increased stone burden, staghorn calculi and longer procedural time 16 .…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of true radiation exposure to surgeons could not be performed because of retrospective data collection and no formal allocation of dosimeters. An informal assessment utilising the study by Park 8 of a 98% lead apron and 97% thyroid shield radiation reduction demonstrates that with a mean of 33 stents per year and median mGy exposure of 11.8 mGy, an annual 12.474 mGy exposure can be calculated from all stents. While this value is compliant with the ARPANSA annual threshold, this is still high considering this calculation only provides an incomplete assessment of true radiation exposure without factors such as distance from the C‐arm or compliance with lead shielding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PARK ET AL. reported a mean fluoroscopy duration of 5.13 min for a mean surgery duration of 83.2 min [12]. However, this fluoroscopy duration can be reduced significantly by optimized operation techniques and protocols [13].…”
Section: A Challenges In Ureteroscopymentioning
confidence: 99%